Stochastic loss of alpha particles in a helias reactor - Kolesnichenko, Ya.I.; Beidler, C.D.; Marchenko, V.S.; Sidorenko, I.N.; Wobig, H. (Вопросы атомной науки и техники, 2000)
Abstract. It is shown that collisionless orbit transformation of the locally trapped particles to the locally passing ones and vice versa in the Wendelstein-line optimized stellarators results in stochastic diffusion of energetic ions. This diffusion can lead to the loss of an essential fraction of energetic ion population from the region where the characteristic diffusion time is small compared to the slowing down time. The loss region and the magnitude of the loss can be minimized by shaping the plasma temperature and density profiles so that they satisfy certain requirements. The predictions of the developed theory are in agreement with the results of numerical modelling of confinementof a-particles in a Helias reactor, which was carried out in this work with the use of the orbit following code. The considered diffusion seems to represent the dominant mechanism of classical losses of a-particles in a Helias reactor.